The debate on workplace absenteeism through the prism of temporary disability. Statistical reality, institutional management and regulatory complexity - Arenas Gómez, Miguel (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
Workplace absenteeism has taken center stage in the political and economic debate. It is frequently approached from a purely macroeconomic perspective that tends to stigmatize temporary disability leave, labeling it as an expense and ignoring any other considerations regarding the benefit. This opinion piece questions the institutional narrative of the AIReF, which advocates for tightening access to the benefit and reducing financial subsidies as a way to control spending. In contrast and based on an analysis of statistical reality and recent legislative reforms concerning temporary disability leave, this article argues for the need to shift the focus to issues outside the economic debate. This approach prioritizes preventive health protection and the optimization of administrative and healthcare management, moving beyond the current, predominantly economic vision.
Keywords: Workplace absenteeism; Temporary Disability; AIReF; Occupational health; Mutual Insurance Societies